The 8th International Conference on Advances in Construction Machinery and Vehicle Engineering ICACMVE 2023 - Halgamuge, Saman K.; Zhang, Hao.; Zhao, Dingxuan; Bian, Yongming; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2024)
This open access book presents select contributions from the 8th International Conference on Advances in Construction Machinery and Vehicle Engineering (ICACMVE 2023), focusing on the recent advances and best practices of Construction Machinery and Vehicle Engineering, related technologies and sciences to meet the challenges in mechanical design, mechanical control and smart manufacturing. The contents focus on design engineering, automation in engineering, construction machinery, intelligence applications, new energy and others. Some of the topics discussed here include advanced manufacturing technologies, industrial engineering and automation, design of mechanical systems, control engineering, automobile engineering, performance analysis of energy systems, thermal modelling and simulations of different systems, optimization and intelligence. The wide range of topics presented in this book will be useful for beginners, researchers, and mechanical engineering professionals.
1. Mechanical Design and Power System Modeling -- 2. Mechanical Control and Fault Monitoring Analysis -- 3. Intelligent Manufacturing and Mechanical Performance Research -- 4. Intelligent Technology Application and Safety Management.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Production engineering; Industrial engineering; Railroad engineering; Mechanical Process Engineering; Industrial and Production Engineering; Rail Vehicles